Dysautonomia in COVID-19 Patients: A Narrative Review on Clinical Course, Diagnostic and Therapeutic Strategies - Carmona-Torre, Francisco; Mínguez-Olaondo, Ane; López-Bravo, Alba; Tijero, Beatriz; Grozeva, Vesselina; Walcker, Michaela; Azkune-Galparsoro, Harkaitz; López de Munain, Adolfo; Alcaide, Ana Belen; Quiroga, Jorge; del Pozo, Jose Luis; Gómez-Esteban, Juan Carlos (Frontiers in Neurology, 2022)
Introduction On March 11, 2020, the World Health Organization sounded the COVID-19 pandemic alarm. While efforts in the first few months focused on reducing the mortality of infected patients, there is increasing data on the effects of long-term infection (Post-COVID-19 condition). Among the different symptoms described after acute infection, those derived from autonomic dysfunction are especially frequent and limiting. Objective To conduct a narrative review synthesizing current evidence of the signs and symptoms of dysautonomia in patients diagnosed with COVID-19, together with a compilation of available treatment guidelines. Results Autonomic dysfunction associated with SARS-CoV-2 infection occurs at different temporal stages. Some of the proposed pathophysiological mechanisms include direct tissue damage, immune dysregulation, hormonal disturbances, elevated cytokine levels, and persistent low-grade infection. Acute autonomic dysfunction has a direct impact on the mortality risk, given its repercussions on the respiratory, cardiovascular, and neurological systems. Iatrogenic autonomic dysfunction is a side effect caused by the drugs used and/or admission to the intensive care unit. Finally, late dysautonomia occurs in 2.5% of patients with Post-COVID-19 condition. While orthostatic hypotension and neurally-mediated syncope should be considered, postural orthostatic tachycardia syndrome (POTS) appears to be the most common autonomic phenotype among these patients. A review of diagnostic and treatment guidelines focused on each type of dysautonomic condition was done. Conclusion Symptoms deriving from autonomic dysfunction involvement are common in those affected by COVID-19. These symptoms have a great impact on the quality of life both in the short and medium to long term. A better understanding of the pathophysiological mechanisms of Post-COVID manifestations that affect the autonomic nervous system, and targeted therapeutic management could help reduce the sequelae of COVID-19, especially if we act in the earliest phases of the disease.